СИСТЕМА УПРАВЛЕНИЯ ЭЛЕКТРОПОТРЕБЛЕНИЕМ ГОРНОРУДНЫХ ПРЕДПРИЯТИЙ С ЦЕЛЬЮ ПОВЫШЕНИЯ ЭЛЕКТРОЭНЕРГОЭФФЕКТИВНОСТИ ДОБЫЧИ ЖЕЛЕЗОРУДНОГО СЫРЬЯ - Синчук, О.Н.; Синчук, И.О.; Бойко, С.Н. (Інститут електродинаміки НАН України, Київ, 2016)
It is investigational factors which determine the level of energy efficiency of iron-ore enterprises. Considered measures on the increase of energy efficiency on the iron-ore enterprises of country. Offered flow diagram of optimum management by electro-consumption of iron-ore enterprise with the purpose of increase of energy efficiency. It is offered, with the purpose of optimum management by an iron-ore enterprise, use of neuronetworks technologies, that in the turn enables real, in spite of much factors, to forecast the level of consumption of power resources, in particular electric power of iron-ore enterprise, by the adaptive control, based on the results of prognostication. References 4, figure 1.